2022
DOI: 10.3390/polym14061240
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Thiazole Derivative on Chitosan Magnetite Nanoparticles for Cadmium Removal—Application for Groundwater Treatment

Abstract: The synthesis and developments of magnetic chitosan nanoparticles for high efficiency removal of the cadmium ions from aquatic medium are one of the most challenging techniques. Highly adsorptive composite (MCH-ATA) was produced by the reaction of chitosan with formaldehyde and amino thiazole derivative. The sorbent was characterized by FTIR, elemental analyses (EA), SEM-EDX, TEM analysis, TGA and titration (volumetric). The modified material includes high nitrogen and sulfur contents (i.e., 4.64 and 1.35 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 62 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The reusability of synthesized NPs in catalytic activity is considered an important factor for industrial applications 79 . Therefore, five sequential cycles were conducted to investigate the efficacy of synthesized Se-NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The reusability of synthesized NPs in catalytic activity is considered an important factor for industrial applications 79 . Therefore, five sequential cycles were conducted to investigate the efficacy of synthesized Se-NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan-bearing amine and hydroxyl groups shift the pK a on the basic side, while the sulfonated groups (in the CH-AS) have an acidic character and shift the pK a values to the acidic direction. Hamza et al reported the pH pzc of different composites based on biopolymers in the range of 2.84 and 4.82 [34,[74][75][76] from 0.1 M NaCl solutions. Sulfonation causes a strong shift in the pH PZC, as noticed in sulfonation of some agriculture wastes (hawthorn kernel), which were shifted from 7 to 3.9 [77].…”
Section: Tga Analysismentioning
confidence: 99%
“…et al reported the pHpzc of different composites based on biopolymers in the range of 2.84 and 4.82 [34,[74][75][76] from 0.1 M NaCl solutions. Sulfonation causes a strong shift in the pHPZC, as noticed in sulfonation of some agriculture wastes (hawthorn kernel), which were shifted from 7 to 3.9 [77].…”
Section: Tga Analysismentioning
confidence: 99%
“…The discharge of effluents from different industries, such as textile and leather tanning, without treatment causes massive harmful effects on the environment [23]. This is due to the highly toxic substances of these effluents, such as dyes and heavy metals [24,25]. Recently, the development of new semiconductors that are used as catalysts for remediation of these effluents are of global interest.…”
Section: Introductionmentioning
confidence: 99%